The structure of the $$f_0(980)$$ f 0 ( 980 ) from system size dependent hadronic resonance ratios in p + p, p + Pb, and Pb + Pb collisions at the LHC - Tom Reichert; Jan Steinheimer; Volodymyr Vovchenko; Christoph Herold; Ayut Limphirat; Marcus Bleicher (European Physical Journal C: Particles and Fields)
Abstract It is shown that the hadronic phase in ultra-relativistic heavy ion collisions can be used to understand the properties of the $$f_0(980)$$ f 0 ( 980 ) resonance. In particular it is shown that the centrality dependence of the $$f_0(980)/\pi $$ f 0 ( 980 ) / π and $$f_0(980)/\phi $$ f 0 ( 980 ) / ϕ ratios depends strongly on the $$f_0(980)\rightarrow {\overline{K}}+K$$ f 0 ( 980 ) → K ¯ + K branching ratio and whether the $$f_0(980)$$ f 0 ( 980 ) is produced as a $$\left| {\overline{q}}q \right\rangle $$ q ¯ q or $$\left| {\overline{s}}s \right\rangle $$ s ¯ s state. These conclusions are drawn from calculations within the partial chemical equilibrium of the HRG model within Thermal-FIST as well as with the fully non-equilibrium hybrid-transport approach UrQMD. Our findings show how the hadronic phase in heavy ion collisions can be used for studies of exotic hadron properties otherwise possible only in dedicated experiments such as PANDA.